IMPLEMENTASI PRINSIP-PRINSIP BUDAYA KERJA APARATUR DI LINGKUNGAN PEMERINTAH DAERAH DI KALIMANTAN - Zakiyah, Siti (Pusjar SKPP Lembaga Administrasi Negara, 2006)
Empirical phenomena show that public accountability and government performance is moderately weak. In that sense, the superlative accomplishment of the state bureaucracy in implementing its task and responsibilities depends not only on the intellectual and managerial capacity, but also on the behavior and organizational culture. This implies that capacity building process has to embrace effort of constructing knowledge and skills as well as good attitude, evenly. In order to strengthen the dimension of work culture in a government institution, State Minister for Apparatus Empowerment (MENPAN) has released many policies, particularly Decree No. 25/KEP/M.PAN/4/2002 concerning Guidance of Extending Work Culture for State Apparatus, from which this paper identifies the current condition and analyses the implementation of work culture principles in the local government institutions in Kalimantan region. Keywords: budaya kerja, aparatur daerah, Kalimantan.